2020
DOI: 10.3389/fmicb.2020.00685
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Immunoglobulin Binding Protein (IbpM) From Mycoplasma pneumoniae

Abstract: Bacteria evolved many ways to invade, colonize and survive in the host tissue. Such complex infection strategies of other bacteria are not present in the cell-wall less Mycoplasmas. Due to their strongly reduced genomes, these bacteria have only a minimal metabolism. Mycoplasma pneumoniae is a pathogenic bacterium using its virulence repertoire very efficiently, infecting the human lung. M. pneumoniae can cause a variety of conditions including fever, inflammation, atypical pneumoniae, and even death. Due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…A highly similar homolog was identified in the closely related species Mycoplasma pneumoniae . Encoded by MPN400 and termed IbpM, this protein was shown to be functionally identical to protein M by Blötz et al in 2020 ( 74 ). In addition, distant homologs have been predicted in Mycoplasma iowae , M. gallisepticum , M. penetrans , Mycoplasma tullyi , Mycoplasma imitans , and Mycoplasma pirum .…”
Section: Mycoplasmas Directly Target the Host Antibodiesmentioning
confidence: 99%
“…A highly similar homolog was identified in the closely related species Mycoplasma pneumoniae . Encoded by MPN400 and termed IbpM, this protein was shown to be functionally identical to protein M by Blötz et al in 2020 ( 74 ). In addition, distant homologs have been predicted in Mycoplasma iowae , M. gallisepticum , M. penetrans , Mycoplasma tullyi , Mycoplasma imitans , and Mycoplasma pirum .…”
Section: Mycoplasmas Directly Target the Host Antibodiesmentioning
confidence: 99%
“…Immunoglobin binding protein (IbpM) is a surface protein encoded by MPN400 that binds strongly to various immunoglobulins (IgM, IgG, and IgA) produced by the host [ 45 ]. Blötz et al demonstrated that IbpM was required by M. pneumoniae to produce cytotoxic effects in host cells and is thus regarded as a virulent factor [ 45 ].…”
Section: Virulence and Pathogenesis Of M Pneumoniaementioning
confidence: 99%
“…Similar to P1, P30 is also an important immunogenic factor [ 130 ]. Mutant M. pneumoniae without the gene encoding P30 is noninfectious and unable to adhere to host cells [ 45 ], which suggests that P30 could potentially be an ideal candidate target for a clinical vaccine. Szczepanek et al created an avirulent P30 adhesin mutant for assessing its efficacy as a live-attenuated vaccine candidate in mice [ 112 ].…”
Section: Development Of Vaccines Against M Pneumoniae mentioning
confidence: 99%
“…mycoids also expresses the MIB and MIP homologous proteins, whereas M. hominis, U. urealyticum, U. parvum, and U. diversum contain the MIB-MIP-encoding genes, but whether these genes are involved in the degradation of IgG remains unknown [103]. In addition, some mycoplasmas, such as M. genitalium and M. pneumoniae, lack the MIB-MIP system, but they can express protein M and DUF31-annotated genes in cells and play a role similar to that of the MIB-MIP system [7,141]. The third mechanism of degrading Ig is the expression of cysteine proteases (CysP).…”
Section: Immunoglobulin Proteasesmentioning
confidence: 99%